2020
DOI: 10.1016/j.annonc.2020.08.1256
|View full text |Cite
|
Sign up to set email alerts
|

1133P Skin photoaging around the site of occurrence of primary melanoma as a clinical predictive biomarker of response to PD-1 inhibitors

Abstract: Background: Cutaneous melanomas have a high tumor mutational burden (TMB) because of mutations induced by ultraviolet radiations (UVR). TMB is a predictive biomarker of response to PD-1 inhibitors but it is unfortunately not yet routinely available. Considering photoaging as a result of repeated and cumulative exposure to UVR, we hypothesized that signs of photoaging around primary melanoma could predict response to PD-1 inhibitors.Methods: We conducted a retrospective bicentric study including 34 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…30 To go even further, we recently proposed pericicatricial sunexposure pattern of the skin around the primary melanoma, as a directly accessible surrogate marker for TMB, to predict response to systemic treatments, in two independent studies including more than 900 patients. 31,32 Another important finding of this study is the positive association between advanced age and higher TMB (P = .002). A few studies reported an association between age and TMB, but these studies encompassed smaller cohorts and covered multiple solid tumors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…30 To go even further, we recently proposed pericicatricial sunexposure pattern of the skin around the primary melanoma, as a directly accessible surrogate marker for TMB, to predict response to systemic treatments, in two independent studies including more than 900 patients. 31,32 Another important finding of this study is the positive association between advanced age and higher TMB (P = .002). A few studies reported an association between age and TMB, but these studies encompassed smaller cohorts and covered multiple solid tumors.…”
Section: Discussionmentioning
confidence: 60%
“… 30 To go even further, we recently proposed pericicatricial sun-exposure pattern of the skin around the primary melanoma, as a directly accessible surrogate marker for TMB, to predict response to systemic treatments, in two independent studies including more than 900 patients. 31 , 32…”
Section: Discussionmentioning
confidence: 99%
“…MM patients with high TMB have more improvement in OS and progression-free survival (PFS) after receiving ICIs (18,19). UV exposure is thought to be the main cause of increased TMB in melanoma (20,21). Dousset et al measured TMB in chronically sun-exposed areas (face and neck), intermittently sun-exposed areas (trunk arms and legs), and sun-protected areas (mucosal, uveal, foot, toes, etc), found that the values of TMB were 37.2 muts/Mb, 13.6 muts/Mb, and 4 muts/Mb successively, and indicated that TMB was significantly associated with sunlight exposure (20).…”
Section: Introductionmentioning
confidence: 99%
“…MM patients with high TMB have more improvement in OS and progression-free survival (PFS) after receiving ICIs ( 18 , 19 ). UV exposure is thought to be the main cause of increased TMB in melanoma ( 20 , 21 ). Dousset et al.…”
Section: Introductionmentioning
confidence: 99%